The Principal's Contribution to the Implementation of Supervision and Work Ethics on the Pedagogic Competence of Padang City Junior High School Teachers - Taufik Hendra; Nurhizrah Gitituati (CV. AFDIFAL MAJU BERKAH, 2022)
Based on the pre-survey in the field, it is shown that the pedagogical competence of Padang City Junior High School teachers is still not optimal. It is suspected to have something to do with implementing the principal's supervision and the teachers' work ethic. Therefore, it is necessary to conduct research to test its validity. This study aims to reveal the contribution of the implementation of principal supervision and work ethic to the pedagogical competence of Padang City Junior High School teachers. The hypotheses proposed in this study are: (1) the implementation of principal supervision contributes to teacher pedagogical competence, (2) work ethic contributes to teacher pedagogical competence, and (3) implementation of principal supervision and cooperation ethos contributes to teacher pedagogical competence. The population in this study were all-state junior high school teachers in the city of Padang, totalling 1,099 people. The research sample of as many as 220 people was taken with a cluster random sampling technique based on the highest national exam results (UN), moderate to the lowest (2019 UN results). The research instrument used is a rating scale and a Likert Scale model questionnaire that has been tested for validity and reliability. The research data were analyzed by correlation and regression techniques. The results of data analysis show that: (1) the implementation of principal supervision contributes to teacher pedagogic competence by 41%, (2) work ethic contributes to teacher pedagogic competence by 52.4%, and (3) implementation of principal supervision and cooperation ethic. Equally, contribute to the pedagogic competence of teachers by 68.5%. The level of achievement of the teacher's pedagogic competence score of 86.71% is in the capable category. For the implementation of principal supervision, 87.63% is in a suitable category, while for the teacher's work ethic, 86.70, the ideal score is in the high category. The above findings imply that the implementation of principal supervision and work ethic are two factors that can improve teachers' pedagogic competence, in addition to other factors.